Pendekatan Pemberdayaan Masyarakat yang Terabaikan: Kelemahan Strategi Mitigasi Bencana BPBD Kabupaten Hulu Sungai Tengah - Perdana, Tiara Selvia; Hamid, Ismar (Prodi Sosiologi FISIP ULM, 2025)
The diverse social and ecological conditions of Hulu Sungai Tengah (HST) Regency require BPBD to apply a more innovative strategic approach in disaster mitigation. This research aims to find out the concrete steps of BPBD HST in reducing the level of vulnerability, the level of vulnerability, and the strategic approach applied in increasing community capacity in disaster management in HST Regency. This research uses a qualitative method with a case study approach. Data were collected through observation, in-depth interviews, and documentation. Data were analyzed using the Manual Data Analysis Procedure (MDAP). The results showed that BPBD HST has implemented various strategies to reduce the level of disaster vulnerability and community vulnerability, as well as increase community and regional capacity, namely: (1) utilizing the ArcGIS application for mapping disaster-prone areas and installing Early Warning Systems (EWS) in strategic locations; (2) paying extra attention to vulnerable groups, such as children, pregnant women, disabilities, and the elderly through the Disaster Resilient Village (Destana) program, as well as specific needs-based assistance during disasters; and (3) increasing community capacity through training in preparing Disaster Management Plan documents, as well as improving technical skills, such as self-evacuation mechanisms, first aid to victims, use of rubber boats and others. This research reveals that the role of BPBD HST in mobilizing resources for disaster mitigation by reducing vulnerability and vulnerability, and increasing capacity through community empowerment to achieve a more ideal strategy in disaster management. This research suggests BPBD HST to further optimize the Destana program by emphasizing the sustainable impact on the HST community, such as organizing routine training, periodic disaster simulations, as well as ongoing mentoring that involves active participation by the local community.